2018
DOI: 10.3329/jbcbm.v4i2.39855
|View full text |Cite
|
Sign up to set email alerts
|

Ex-situ conservation of threatened forest tree species for sustainable use of forest genetic resources in Bangladesh

Abstract: The present study was carried out to advance towards the conserving threatened forest tree species of Bangladesh under ex-situ conservation system. Four thousand plants of forty eight threatened forest tree species were conserved at three areas, namely Institute of Forestry and Environmental Sciences, Chittagong University; Radar Unit of Bangladesh Air Force, Cox"s Bazar; and the Keochia research station of Bangladesh Forest Research Institute. The average 90-95% plants survived in each conservation site and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Even 75 medicinal plant species only under the two families (Apocynaceae and Vitacease) and 28 species to be threatened due to habitat destruction and over exploitation [28]. In addition, 94 of 179 species of Orchidaceae and 26 of 86 species of Lamiaceaeae are threatened [29].…”
Section: Threatened Plant Speciesmentioning
confidence: 99%
“…Even 75 medicinal plant species only under the two families (Apocynaceae and Vitacease) and 28 species to be threatened due to habitat destruction and over exploitation [28]. In addition, 94 of 179 species of Orchidaceae and 26 of 86 species of Lamiaceaeae are threatened [29].…”
Section: Threatened Plant Speciesmentioning
confidence: 99%
“…According to M.M. Rahman et al (2018), ex situ conservation of endangered species of checker tree is important for sustainable use of forest genetic resources in Ukraine. N.P.…”
Section: Introductionmentioning
confidence: 99%
“…Khasis are the aboriginal inhabitants of the Khasi-Jaintia Hills who migrated westward and encroached upon the Khasi-Jaintia Hills (Bhattacharjee, 1984). Even though the exact time of Khasi-Jaintia Kingdom formation still has not been pinpointed, few ethnologists suggested that Jaintia Kingdom was established in 1500 A.D. which then gradually undertook the areas of present Sylhet, Sunamgonj, parts of Moulvibazar and Habiganj Districts (Rahman et al, 2018). Jaintiapur, the capital of the Khasi-Jaintia kingdom (1500 AD to 1835 AD) was geographically located inside the Sylhet Division of Bangladesh.…”
mentioning
confidence: 99%